2015
DOI: 10.1128/ec.00034-14
|View full text |Cite
|
Sign up to set email alerts
|

VibA, a Homologue of a Transcription Factor for Fungal Heterokaryon Incompatibility, Is Involved in Antifungal Compound Production in the Plant-Symbiotic Fungus Epichloë festucae

Abstract: Symbiotic association of epichloae endophytes (Epichloë/Neotyphodium species) with cool-season grasses of the subfamily Pooideae confers bioprotective benefits to the host plants against abiotic and biotic stresses. While the production of fungal bioprotective metabolites is a well-studied mechanism of host protection from insect herbivory, little is known about the antibiosis mechanism against grass pathogens by the mutualistic endophyte. In this study, an Epichloë festucae mutant defective in antimicrobial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…A culture filtrate was found to inhibit conidial germination of the plant pathogen D. erythrospila. It was previously shown that the activity was 10 times as high as that of the original E437 strain [14]. The active filtrates were subjected to three-steps purification: (1) cation exchange resin (Amberlite-IRC 76), (2) reversed-phase HPLC (ODS column), and (3) normal-phase HPLC (HILIC column), affording an active substance in the yield of 38.6 mg/L.…”
Section: Chemical Identification Of An Antifungal Substance Produced mentioning
confidence: 99%
See 2 more Smart Citations
“…A culture filtrate was found to inhibit conidial germination of the plant pathogen D. erythrospila. It was previously shown that the activity was 10 times as high as that of the original E437 strain [14]. The active filtrates were subjected to three-steps purification: (1) cation exchange resin (Amberlite-IRC 76), (2) reversed-phase HPLC (ODS column), and (3) normal-phase HPLC (HILIC column), affording an active substance in the yield of 38.6 mg/L.…”
Section: Chemical Identification Of An Antifungal Substance Produced mentioning
confidence: 99%
“…We previously identified E. festucae strain E437 as a producer of antifungal substance against several grass pathogens such as Drechslera erythrospila, Colletotrichum graminicola, and Bipolaris sorokiniana [13]. We have isolated a mutant that had lost antifungal activity by random mutagenesis, and a transcription factor VibA was identified as an essential factor for the production of the antifungal activity [14]. Fungal VibA homologs (also known as VIB-1) are NDT80/PhoG-type transcription factors that regulate a wide range of genes involved in the vegetative incompatibility, conidiation, formation of aerial hyphae, development of female reproductive structure, and production of extracellular protease [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement in multiple, seemingly unrelated processes has been reported for VIB-1, including the regulation of protoperithecial development, vegetative incompatibility and programmed cell death, regulation of responses to nitrogen and carbon starvation, as well as plant cell wall degradation by carbon catabolite repression (Dementhon et al, 2006;Hutchison and Glass, 2010;Xiong et al, 2014). In the endophytic plant-symbiont Epichloë festucae (Sordariomycetes), VIB-1 is involved in the production of antifungal compounds (Niones and Takemoto, 2015).…”
Section: N-acetylglucosamine Catabolism Inmentioning
confidence: 99%
“…The spectrum of epichloëcyclins produced varies between different endophyte strains as a result of differences in encoded GigA sequences; for example, epichloëcyclins A–N have been characterized, but only A–E are present in plants infected with E. festucae strain Fl1 (Johnson et al , 2015). Epichloë species are also known to protect the host, to varying degrees, from a range of fungal pathogens (Gwinn & Gavin, 1992; Bonos et al , 2005; Clarke et al , 2006; Steinebrunner et al , 2008; Niones & Takemoto, 2014, 2015; Tian et al , 2017). In addition to protection from these biotic stresses, Epichloë endophytes also protect hosts from abiotic stresses such as drought (Arachevaleta et al , 1989; Hahn et al , 2007) although the physiological basis of this phenomenon is not known.…”
Section: Introductionmentioning
confidence: 99%